Syntactic Tree Diagram: Students' Error in Constructing Tree Diagram for Phrase and Sentence Level - Uspayanti, Rezky; Monika, Santy; Indriyani, Novi; Narahawarin, Margaretha Febriany (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Syntax is the study about the pattern of the language and mastery of syntax plays a crucial role in understanding grammatically correct English. This research aims to investigate the common errors made by students when constructing tree diagrams for phrases and sentences. The research employed a descriptive qualitative method. There were eight students involved in this research who took the syntax class from the English Education Department at Musamus University. Data were collected through written tests in which students were asked to construct tree diagrams for noun phrases, verb phrases, prepositional phrases, and sentences. The result showed that students got difficulty in constructing tree diagram for sentence level and prepositional phrase level. The findings show varying levels of student performance. For phrase level analysis, 100% of students correctly constructed the tree diagram for a noun phrase, and 87.5% succeeded with the verb phrase. However, only 37.5% accurately analyzed the prepositional phrase, indicating significant difficulty with this type. At the sentence level, accuracy dropped further: 75% of students made errors in constructing tree diagrams for more complex sentences such as "The beautiful girl cares of her cat" and "The smart students in the library are smiling gaily", while 87.5% made errors on a simpler sentence, "I have one sister". These results suggest that while students generally grasp phrase structures, they struggle with full sentence constructions and hierarchical syntactic patterns. The study highlights the need for more focused instruction and practice in sentence-level syntax and tree diagram construction to improve students’ analytical skills and grammatical proficiency.